Ticagrelor monotherapy in patients with chronic kidney disease undergoing percutaneous coronary intervention: TWILIGHT-CKD. (23rd August 2021) - Stefanini, Giulio G; Briguori, Carlo; Cao, Davide; Baber, Usman; Sartori, Samantha; Zhang, Zhongjie; Dangas, George; Angiolillo, Dominick J; Mehta, Shamir; Cohen, David J; Collier, Timothy; Dudek, Dariusz; et al.
Abstract: Aims: The aim of this study was to assess the impact of chronic kidney disease (CKD) on the safety and efficacy of ticagrelor monotherapy among patients undergoing percutaneous coronary intervention (PCI). Methods and results: In this prespecified subanalysis of the TWILIGHT trial, we evaluated the treatment effects of ticagrelor with or without aspirin according to renal function. The trial enrolled patients undergoing drug-eluting stent implantation who fulfilled at least one clinical and one angiographic high-risk criterion. Chronic kidney disease, defined as an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2, was a clinical study entry criterion. Following a 3-month period of ticagrelor plus aspirin, event-free patients were randomly assigned to aspirin or placebo on top of ticagrelor for an additional 12 months. Of the 6835 patients randomized and with available eGFR at baseline, 1111 (16.3%) had CKD. Ticagrelor plus placebo reduced the primary endpoint of Bleeding Academic Research Consortium (BARC) type 2, 3, or 5 bleeding as compared with ticagrelor plus aspirin in both patients with [4.6% vs. 9.0%; hazard ratio (HR) 0.50, 95% confidence interval (CI) 0.31–0.80] and without (4.0% vs. 6.7%; HR 0.59, 95% CI 0.47–0.75; P interaction  = 0.508) CKD, but the absolute risk reduction was greater in the former group. Rates of death, myocardial infarction, or stroke were not significantly different between the two randomized groups irrespective of the presence (7.9% vs. 5.7%; HR 1.40, 95% CI 0.88–2.22) or absence of (3.2% vs. 3.6%; HR 0.90, 95% CI 0.68–1.20; P interaction  = 0.111) CKD. Conclusion: Among CKD patients undergoing PCI, ticagrelor monotherapy reduced the risk of bleeding without a significant increase in ischaemic events as compared with ticagrelor plus aspirin. Graphical Abstract: